Risky Sexual Practices and Associated Factors for HIV/AIDS Infection among Private College Students in Bahir Dar City, Northwest Ethiopia. (12th March 2013) - Alamrew, Zelalem; Bedimo, Melkamu; Azage, Muluken
Abstract : Background . Adolescents and young adults engage in risky sexual behaviours that may expose them to risk of contracting sexual transmitted diseases. The aim of this study was to assess risky sexual practices and associated factors for HIV/AIDS infection. Methods . A cross-sectional study was conducted in March 2012 among 790 college students. Self-administered questionnaire was used to collect the data. The data were analyzed using univariate, bivariate, and multivariate analyses with SPSS version 16 software package. Results . About 40.6% of sexually active respondents had risky sexual behaviours. Multiple sexual partners and unprotected sex were reported by 45.3% and 38.4% of sexually active respondents. Having multiple sexual partners was associated with alcohol use (AOR = 3.20; 95% CI: 2.02–5.08) and having a close friend who started sex (AOR = 5.99; 95% CI: 3.66–9.81). Unprotected sex was associated with marital status (AOR = 2.68; 95% CI: 1.55–4.64), alcohol intake (AOR = 2.19; 95% CI: 1.36–3.54), and frequency of visiting night clubs (AOR = 0.25; 95% CI: 0.12–0.52) for those who visit occasionally and (AOR = 0.45; 95% CI: (0.21–0.97) for those who visited at least once a week. Conclusion . Large proportions of students engaged in risky sexual behaviours and various risk factors were associated with risky sexual behaviours. Therefore, interventions targeting on alcohol intake, peer pressure, and attending night clubs are recommended.